Гистология пищеварительной системы клеща Androlaelaps casalis (Gamasoidea, Parasitiformes) - Старовир, И.С. (Вестник зоологии, 1980)
Structure and morphofunctional changes of gut epithelial cells are described for hungry and replete mites Androlaelaps casalis. It is determined that owing to extensibility of the gut cells, the guts can take a considerable amount of food.